Le juge : censeur de l'action de l'Administration - Brown, L.; McNicoll, Micheline (Les Cahiers de droit, 1984)
As Professor Wade rightly reminds us : « The powerful engines of authority must be prevented from running amok ». The control of the legality of administrative action by the ordinary courts prevents such action being arbitrary or unreasonable. But in sitting in judgment upon the administration, does not the judge risk usurping the role of the administrator ? This is a real misgiving which many authors share : they complain of « Government by judges ». The present article (based upon a public lecture delivered at Laval University in October 1983) considers this aspect of judicial control, especially in relation to certain recent decisions of the English superior courts.